MEASURING UNDERSTANDING OF ANOVA MATERIAL THROUGH THE FLIPPED CLASSROOM LEARNING METHOD - Adnyani, Luh Putu Widya; Wiyanti, Wiwik (Jurnal Review Pendidikan dan Pengajaran, 2024)
During the Covid-19 pandemic, student learning is done from home with online learning. Many teachers use methods to adjust learning from face-to-face to face-to-face online. One of the learning methods used is the flipped classroom. In several studies, this method has been able to improve students' mathematics skills. Based on this background, researchers are interested in examining the effectiveness of using the flipped classroom method in ANOVA learning at the university level. The subjects of this study were students of the land transportation study program at STTD Bekasi and statistics at Matana University. The number of research subjects was 14 students. The data analysis method used was the non-parametric sign test to paired population method. From the analysis carried out, the results showed that the flipped classroom method applied resulted in a significant increase in students' ANOVA material learning outcomes.